A persuasão na propaganda e a criação de mundo textual sob a perspectiva da linguística sistêmico-funcional - Omaki, Marisa de Mitri Ruiz (2010)
The creative potential of advertising as a type of genre that calls forth imaginary situations intended to persuade has been dealt with by many authors (CARTER; NASH, 1990, COOK, 1992, 1994, SEMINO, 1997, apud DOWNING, 2003). This is partly due to the fact that current advertising is less interested in listing objective properties of objects than linking the product to another entity, effect or person, making a fusion that ends up involving a featureless product in desirable properties . By the way, Downing (2003) talks about making a textual world in advertising, world in which the choices of the linguistic system give different interpretations of reality, that is, they present different views of the world. The objective of my research is, thus, examining persuasion in advertising, through checking the resources used to make the textual world. Therefore, I resort to Fowler´s Critical Linguistics (Fowler 1991) and to Fairclough´s Critical Discourse Analysis (Fairclough 1992), which indicate that Functional Systemic Linguistics is the adequate methodology for this type of analysis